Minimally Invasive Surgical Techniques for the Treatment of Dogs with Urinary Incontinence Due to Ureteral Ectopia - Przemysław Prządka; Bartłomiej Liszka; Wojciech Krajewski; Sylwester Gerus; Ludwika Gąsior; Agnieszka Antończyk; Piotr Skrzypczak; Dominika Kubiak-Nowak; Mateusz Hebel; Kamil Suliga; Zdzisław Kiełbowicz; Dariusz Patkowski (Life)
Ectopic ureters are uncommon congenital abnormalities in dogs, leading to urinary incontinence. Ectopic ureters can be intramural or extramural. Intramural is usually the more prevalent form. Female dogs are affected more often than male dogs. This disease requires the surgical correction of the ureters. Three surgical techniques have been described in this regard: neoureterostomy, nephroureterectomy, and ureteroneocystostomy. In this study, we present minimally invasive surgical procedures for treating extra- and intramural ectopic ureters. Sixteen client-owned dogs with clinical signs of urinary incontinence due to ectopic ureters underwent surgery. Laparoscopic ureteroneocystostomies were performed to correct three extramural cases and one atypical intramural case of ectopic ureters. Additionally, cystoscopically guided laser ablation was used to correct 12 cases of intramural ectopic ureters. In all cases, the procedures were achieved without the need for conversion to open surgery. Among the minor complications, slight hematuria and a few cases of cystitis, which responded to conservative treatment, were noted. Major postoperative complications were not observed. Only one out of sixteen dogs failed to regain urinary continence, but it responded to pharmacological treatment. In conclusion, cases of ectopic ureters may benefit from minimally invasive surgical techniques when their use is feasible.